Tibial plateau fracture: anatomy, diagnosis and management. (2nd October 2020) - Rudran, Branavan; Little, Christopher; Wiik, Anatole; Logishetty, Kartik
Abstract : Tibial plateau fractures are peri-articular knee fractures of the proximal tibia. The presentation is dependent on the mechanism of injury. The tibial plateau is the bony platform of the distal half of the knee joint, and is made up of a medial and lateral condyle separated by the intercondylar eminence. The presentation of tibial plateau fractures can vary greatly as a result of the bimodal mechanism of injury and patient characteristics. The patient should be assessed for life- and limb-threatening injuries in accordance with British Orthopaedic Association Standards of Trauma guidelines. Imaging is undertaken to understand configuration of the fracture, which is classified by the Schatzker classification. Definitive management of the fracture depends on the severity, ranging from conservative to surgical management. Surgery is required for more severe tibial plateau fractures to restore articular congruity, mechanical alignment, ligamentous stability and to permit early mobilisation. Medium-term functional outcome after tibial plateau fractures is generally excellent when anatomy and stability is restored. At least half of patients return to their original level of physical activity. Surgical management of tibial plateau fractures is not without complication. Risk factors include postoperative arthritis, bicondylar and comminuted fractures, meniscal removal, instability, malalignment and articular incongruity. Tibial plateau fractures account for 1% of all fractures, and typically occur either as a fragility fracture or secondary to a high-energy impact. These latter injuries are associated with extensive soft tissue injury, life- and limb-threatening complications and long-term sequelae. While outcomes are generally good, severe injuries are at higher risk of infection and post-traumatic arthritis requiring knee arthroplasty. This article considers the anatomy, diagnosis and evidence-based management strategies for tibial plateau fracture.